Comparison between Crown-to-Root Ratio and Crown-to-Implant Ratio in Natural Teeth - Anita Tiwari; Leena Tomer; Bina Kumari; Arya Gupta; Kunal Raj; Sambit Prasad (Journal of Pharmacy and Bioallied Sciences)
Background: In locations with poor bone quality and significant masticatory pressures, bone resorption after tooth loss inhibits implant implantation. This condition requires augmentation or short implants. Materials and Methods: Fifty low-bone-height patients had single-tooth implants and were observed for 12 months. Radiographs examined crown height, crown-to-implant ratio, and marginal bone loss at baseline, six months, and 12 months. The correlation between crown height and marginal bone loss was examined. Results: The average crown-to-implant ratio was 1.8:1 in the study. Implant crown heights above 10 mm showed increased marginal bone loss. The mean marginal bone loss at six months was 0.25 ± 0.08 mm, rising to 0.38 ± 0.10 mm at 12 months. Implants with crown heights ≤10 mm had considerably reduced bone loss (P < 0.05) compared to implants with greater crown heights. Optimized crown height distributed lateral stresses for improved clinical results and implant stability. Conclusion: Implant-supported prostheses depend on crown height for lateral force distribution and marginal bone preservation. Implants ≤10 mm crown height showed decreased marginal bone loss and improved treatment results.